Anomalous Reduction of the Total Suspended Matter During the COVID-19 Lockdown in the Hooghly Estuarine System - Jayaram, Chiranjivi; Roy, Rajdeep; Chacko, Neethu; Swain, Debadatta; Punnana, Ramunaidu; Bandyopadhyay, S.; Choudhury, S. B.; Dutta, Dibyendu (Frontiers in Marine Science, 2021)
Impact of COVID-19 lockdown in the Hooghly estuarine region, India, is assessed using the Total Suspended Matter (TSM) concentration. Estimation of TSM is performed using Landsat 8/OLI and an inter-comparison of TSM load during the pre-lock down and lockdown period is done. It is observed that during the lockdown period, TSM reduced by 30 - 50%. This is a significant observation considering the ecological balance of the region and the fact that it is home to the largest mangroves in the world. This change in suspended matter presumably reflects the influence of reduction in anthropogenic activities owing to COVID-19 lockdowns such as industries, closure of shipping activities (through less dredging) and brick kilns (through less sediment removal), which are generally the primary contributors in this region. Even though, these observed changes are representative of the positive influence of COVID-19 lockdown, its implications in estuarine biogeochemistry still remains poorly quantified. Decrease in TSM content may increase light penetration thereby increasing the primary productivity. In addition, low sediment load reaching the Bay of Bengal could influence the carbon export due to reduction in ballasting effect as reported from this region. In summary, the influence of COVID-19 lockdown on the biogeochemistry of the aquatic ecosystem appears rather complex than thought earlier and may vary regionally based on local hydrodynamics. The analysis elucidates the complex interplay of regional lockdown and its implication in modulation of local biogeochemistry. However, the relative importance of each process in the Hooghly estuary remains to be fully evaluated.